Genomic Plasticity Enables a Secondary Electron Transport Pathway in Shewanella oneidensis - Schicklberger, M. (American Society for Microbiology, 2013)
Microbial dissimilatory iron reduction is an important biogeochemical process. It is physiologically challenging because iron occurs in soils and sediments in the form of insoluble minerals such as hematite or ferrihydrite. Shewanella oneidensis MR-1 evolved an extended respiratory chain to the cell surface to reduce iron minerals. Interestingly, the organism evolved a similar strategy for reduction of dimethyl sulfoxide (DMSO), which is reduced at the cell surface as well. It has already been established that electron transfer through the outer membrane is accomplished via a complex in which β-barrel proteins enable interprotein electron transfer between periplasmic oxidoreductases and cell surface-localized terminal reductases. MtrB is the β-barrel protein that is necessary for dissimilatory iron reduction. It forms a complex together with the periplasmic decaheme c-type cytochrome MtrA and the outer membrane decaheme c-type cytochrome MtrC. Consequently, mtrB deletion mutants are unable to reduce ferric iron. The data presented here show that this inability can be overcome by a mobile genomic element with the ability to activate the expression of downstream genes and which is inserted within the SO4362 gene of the SO4362-to-SO4357 gene cluster. This cluster carries genes similar to mtrA and mtrB and encoding a putative cell surface DMSO reductase. Expression of SO4359 and SO4360 alone was sufficient to complement not only an mtrB mutant under ferric citrate-reducing conditions but also a mutant that furthermore lacks any outer membrane cytochromes. Hence, the putative complex formed by the SO4359 and SO4360 gene products is capable not only of membrane-spanning electron transfer but also of reducing extracellular electron acceptors.